Factors Associated with Menstrual Cycle in Female Students at Al-Hidayah Islamic Boarding School Depok - Kadek Ayu Dessyana; Iin Fatmawati; Marjan, Avliya Quratul; Firlia Ayu Arini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Menstrual disorders are still a problem which is often found. In Indonesia, the prevalence of menstrual cycle disorders in adolescent females is 11.7%. It can occur due to several factors; such as, imbalanced nutritional intake, the level of academic stress experienced by adolescent, and sleep quality. If menstrual cycle disorders are not treated properly, it can affect the quality of life related to health; such as, increasing the risk of various uterine cancers, bone fractures and infertility. The aim of this study is that to analyze the relationship between protein, fat intake, academic stress levels and sleep quality with menstrual cycle in adolescent females at the Al-Hidayah Islamic Boarding School. This study was a quantitative study by using a cross sectional study design. The sampling technique was stratified random sampling with a sample size of 104 respondents. Moreover, the data in this study was obtained from filling out questionnaires and interviews. Meanwhile, bivariate analysis was conducted by using the chi square test. The results of the chi square test shows that there is a significant relationship between protein intake (p-value = 0.026) and fat intake (p-value = 0.029) with the menstrual cycle. Meanwhile, variables which are not related are academic stress level (p-value = 0.0.491) and sleep quality (p-value = 0.5). It is expected to be more paid attention to food intake based on balanced nutrition